Projeto UCA em Mato Grosso : práticas de leitura e escrita - Silva, Enilda Euzébio da (2013)
This study looked forward to discuss the useful of the ICT (Information and Communication Technology) in Education. This study aims to analyze the laptop as a useful tool to the pedagogical practices. In order to discuss the Information and Communication Technology, specially the laptops that are being integrated to the pedagogical practices in one of the experiments, the One Laptop per Children Program, in the State of Mato Grosso, it was necessary to know the pedagogical practices applied to the development of reading and writing abilities, through the use of the educational laptop, performed in the Portuguese Language subject by students of basic education. This study is important because the use of the technological resources in schools, mainly the laptop and the possibility to get information through the internet, request discussion and critical reflection by the people who are responsible for school education. This study employs the qualitative research as methodology with the Case Study. A questionnaire, in loco observation, the document analysis and the interview were used as tools to collect data. The results revealed that the introduction of the Information and Communication Technology in Education is not a simple task. It is necessary a great effort by those who are interested in the use of the Information and Communication Technology in Education. If the technical benefits of these resources were not critically analyzed, the effort to use the Information and Communication Technology in schools can be useless and can contribute even more to the development of a superficial work with the language. Thus, it is not enough offer technological and digital equipment to public schools if these resources were not properly connected with the learning purpose. Among other aspects, it is necessary a continuing education policy according to the schools reality, in order to the teachers, who have an important responsibility in this process, feel confident and prepared to use the Information and Communication Technology as a pedagogical resource.